Creating and appropriating value in collaborative relationships - Wagner, Stephan M; Eggert, Andreas; Lindemann, Eckhard (Journal of business research)

Kundenbindung auf Basis des Relationship Value - Eggert, Andreas; Garnefeld, Ina (Handbuch Kundenbindungsmanagement)

Explanatory factors for firms’ use of temporary agency work in Germany - Thommes, Kirsten; Weiland, Katrin (European Management Journal)

Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten

Individuelle Bildungsgänge im Berufsbildungssystem - Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Rollenbasierte Kompetenzbilanz - Potenziale und Herausforderungen für das berufsschulische Übergangssystem - Frehe, Petra; Kremer, H.-Hugo (Funktionen und Erträge pädagogischer Diagnostik im wirtschafts- und berufspädagogischen Bereich)

On the equivalence of Nash and evolutionary equilibrium in finite populations - Hehenkamp, Burkhard; Possajennikov, Alex; Guse, Tobias (Journal of Economic Behavior & Organization)

Strategic Unemployment - Angerhausen, Julia; Bayer, Christian; Hehenkamp, Burkhard (Journal of Institutional and Theoretical Economics (JITE))

TCO-as-a-Service --- Servicebasierte Lebenszyklusrechnung für hybride Leistungsbündel - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver; Müller, Steffen (Vertriebsinformationssysteme --- Standardisierung, Individualisierung, Hybridisierung und Internetisierung)

E-Services im Handel --- Auffindung und Dokumentation von Potenzialen zur Digitalisierung von Dienstleistungen für Hersteller und Kunden - Beverungen, Daniel; Knackstedt, Ralf; Winkelmann, Axel (Vertriebsinformationssysteme --- Standardisierung, Individualisierung, Hybridisierung und Internetisierung)

Vermarktung hybrider Leistungsbündel - Weddeling, Matthias; Steiner, Michael; Müller, Oliver; Knackstedt, Ralf; Becker, Jörg; Backhaus, Klaus; Beverungen, Daniel; Frohs, Margarethe

PAS 1091: Schnittstellenspezifikationen zur Integration von Sach- und Dienstleistung. - Institut für Normung e.V., Deutsches

Handels- und steuerrechtliche Kapitalkontenfortschreibung und deren Einfluss auf die Verlustverrechnung bei Personengesellschaften - Kopplin, Anja; Maßbaum, Alexandra; Sureth-Sloane, Caren (Die Wirtschaftsprüfung)

Der Einfluss von Thin Capitalization Rules auf unternehmerische Kapitalstrukturentscheidungen - Maßbaum, Alexandra

Empirische Analyse der Unternehmensbewertung für die Erbschaftsteuer mit dem vereinfachten Ertragswertverfahren - Müller, Jens; Sureth-Sloane, Caren

Mögliche Fallstricke einer Optimierung unternehmerischer Investitionsentscheidungen auf der Grundlage der Konzernsteuerquote - Müller, Jens; Sureth-Sloane, Caren; Läufer, Christian (Die Wirtschaftsprüfung)

The Impact of Profit Taxation on Capitalized Investment with Options to Delay and Divest - Schneider, Georg; Sureth-Sloane, Caren

Beteiligungsveräußerungen und Abgeltungssteuer - Sureth-Sloane, Caren (Besteuerung, Rechnungslegung und Prüfung der Unternehmen)

Wichtigste Einflussfaktoren auf die steuerliche Verlustnutzung bei Personengesellschaften - Sureth-Sloane, Caren (Steuer und Studium)

Welchen Einfluss hat die Anwesenheit von ausländischen und multinationalen Unternehmungen auf die deutschen Exporte? - Gilroy, Bernard Michael; Lukas, Elmar; Heimann, Christian

Effizienz Deutscher Krankenhäuser im Zeitablauf - Schmitz, Hendrik; Augurzky, B.

Die Wirkung ausländischer Direktinvestitionen auf die Beschäftigung im Heimatmarkt: Eine empirische Analyse des deutschen Mittelstands. - Zapkau, F B; Schwens, C; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Enlarging the Focus on the Role of Competencies, Abilities, and Personality in Management Research. - Steinmetz, Holger; Schwens, C; Isidor, R; Kabst, Rüdiger (Management Revue: The International Review of Management Studies.)

Internationalisierung junger Technologieunternehmen: Auslandsmärkte und Erfolgsimplikationen. - Schwens, C; Kabst, Rüdiger (Die Betriebswirtschaft (DBW).)

Subjective Health and its Relationship with Working Time and Job Stressors: Sequence or General Factor Model?. - Steinmetz, Holger; Schmidt, P (Work and Stress.)

Measuring eTrust in distributed systems - General Concept and Application to Internet Voting - Volkamer, Melanie; Schryen, Guido (Proceedings of the 23rd Bled eConference)
Emerging digital environments and infrastructures, such as distributed services and computing services, have generated new options of communication, information sharing, and resource utilization in past years. Different distributed trust concepts are applied to increase trust in such systems. However, these concepts yield to rather complex architectures which make it difficult to determine which component or system needs to be trusted. This paper presents a novel trust measurement method for distributed systems which enables the t identification of weak points in the overall system architecture. The measurement method includes the specification of a formal trust language and its representation by means of propositional logic formulas. The applicability of the proposed concepts is demonstrated by conducting a case study on the Internet voting system that was used in the 2007 parliamentary elections in Estonia.
Keywords: distributed trust concepts; measuring etrust; Internet voting

Increasing software security through open source or closed source development? Empirics suggest that we have asked the wrong question - Schryen, Guido; Eliot, Rich (43rd Annual Hawaii International Conference on System Sciences)
While many theoretical arguments against or in favor of open source and closed source software development have been presented, the empirical basis for the assessment of arguments and the development of models is still weak. Addressing this research gap, this paper presents the first comprehensive empirical investigation of published vulnerabilities and patches of 17 widely deployed open source and closed source software packages, including operating systems, database systems, web browsers, email clients, and office systems. The empirical analysis uses comprehensive vulnerability data contained in the NIST National Vulnerability Database and a newly compiled data set of vulnerability patches. The results suggest that it is not the particular software development style that determines the severity of vulnerabilities and vendors? patching behavior, but rather the specific application type and the policy of the particular development community, respectively.

A decision-theoretic foundation of IS business value research - Schryen, Guido; Bodenstein, Christian (Proceedings of the 18th European Conference on Information Systems (ECIS 2010))
Enduring doubts about the value of IS investments reveal that IS researchers have not fully managed to identify and to explain the economic benefits of IS. Three research tasks are essential requisites on the path towards addressing this criticism: the synthesis of knowledge, the identification of lack of knowledge, and the proposition of paths for closing knowledge gaps. This paper considers each of these tasks by a) synthesizing key research findings based on a comprehensive literature review, b) identifying and unfolding key limitations of current research, and c) applying a decision-theoretic perspective, which opens new horizons to IS business value research and shows paths for overcoming the limitations. The adoption of this perspective results in a decision-theoretic foundation of IS business value research and includes the proposition of a consistent terminology and a research model that frames further research.
Keywords: Decision theory; IT value; IS assessment; IS evaluation

A Fuzzy Model for IT Security Investments - Schryen, Guido (Sicherheit 2010 : Sicherheit, Schutz und Zuverlässigkeit ; Konferenzband der 5. Jahrestagung des Fachbereichs Sicherheit der Gesellschaft für Informatik e.V. (GI), 5. - 7. Oktober 2010 in Berlin)
This paper presents a fuzzy set based decision support model for taking uncertainty into account when making security investment decisions for distributed systems. The proposed model is complementary to robabilistic approaches and useful in situations where probabilistic information is either unavailable or not appropriate to reliably predict future conditions. We ?rst present the speci?cation of a formal security language that allows to specify under which conditions a distributed system is protected against security violations. We show that each term of the security language can be transformed into an equivalent propositional logic term. Then we use propositional logic terms to de?ne a fuzzy set based decision model. This optimization model incorporates uncertainty with regard to the impact of investments on the achieved security levels of components of the distributed system. The model also accounts for budget and security constraints, in order to be applicable in practice.

An Analysis of Literature Reviews on IS Business Value: How Deficiencies in Methodology and Theory Use Resulted in Limited Effectiveness - Schryen, Guido (Proceedings of the First Scandinavian Conference on Information Systems (SCIS))
Enduring doubts about the value of IS investments reveal that IS researchers have not fully managed to identify and to explain the economic benefits of IS. This paper assumes that literature reviews, which represent a powerful instrument for the identification and synthesis of knowledge, have not tapped their full potential to address this issue due to deficiencies in methodology. The analysis of 18 literature reviews published in pertinent academic outlets during the past 20 years shows such deficiencies. Two of the most critical weaknesses identified are (1) the lack of theory use in most reviews and (2) a weak linkage of reviews, resulting in little progress in theory and framework development. The systematic identification of these weaknesses and the extraction of promising methodological examples from past literature are the main contributions of this work, which supports the composition of more effective literature reviews in future research.
Keywords: Literature review; Business value; Information systems; Methodology; Theory

Preserving knowledge on IS business value: what literature reviews have done - Schryen, Guido (Business & Information Systems Engineering (BISE))
The economic relevance of information systems has been studied for many years and has attracted an abundance of research papers. However, the ?productivity paradoxon? of the 90s, Carr?s widely recognized paper ?IT doesn?t matter?, and several studies that do not find a positive correlation between IS investments and economic performance reveal long-lasting difficulties for IS researchers to explain ?IS business value?. Business executives and researchers also continue to question the value of IS investments. This raises the question of whether literature reviews have tapped their potential to address the concerns by covering key research areas of IS business value and preserving their key findings. In order to address this question, this paper identifies and describes 12 key research areas, and synthesizes what literature reviews published in pertinent academic outlets have done to preserve knowledge. The analysis of 22 literature reviews shows that some crucial areas have not been (sufficiently) covered. They provide fertile areas for future literature reviews. As this work is based on the results of more than 200 research papers, it is capable of drawing a comprehensive picture of the current state-of-the-art in IS business value research.
Keywords: Business value; Information systems; Literature review; Meta review

Ökonomischer Wert von Informationssystemen - Beitrag von Literatur-Reviews zum Wissenserhalt ( = Preserving Knowledge on IS Business Value. What Literature Reviews Have Done) - Schryen, Guido (Wirtschaftsinformatik)
The economic relevance of information systems has been studied for many years and has attracted an abundance of research papers. However, the ?productivity paradoxon? of the 1990s, Carr?s widely recognized paper ?IT doesn?t matter?, and several studies that do not find a positive correlation between IS investments and economic performance reveal long-lasting difficulties for IS researchers to explain ?IS business value?. Business executives and researchers also continue to question the value of IS investments. This raises the question of whether literature reviews have tapped their potential to address the concerns by covering key research areas of IS business value and preserving their key findings. In order to address this question, this paper identifies and describes 12 key research areas, and synthesizes what literature reviews published in pertinent academic outlets have done to preserve knowledge. The analysis of 22 literature reviews shows that some crucial areas have not been (sufficiently) covered. They provide fertile areas for future literature reviews. As this work is based on the results of more than 200 research papers, it is capable of drawing a comprehensive picture of the current state-of-the-art in IS business value research.

Educational change and innovative teaching practice: a study of the impact of reforms on the work of lectures in vocational education and training in England and Germany - Ertl, H.; Kremer, H.-Hugo (Orbis Scholae, Educational Change in the global context)

Individuelle Förderung zur Kompetenzentwicklung in der beruflichen Bildung - Überlegungen zur Grundlegung eines Forschungs- und Entwicklungsbereichs - Kremer, H.-Hugo; Zoyke, A. (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Neue Medien als Katalysator individueller Förderung in der Berufsbildung - Kremer, H.-Hugo (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Individuelle Förderung im Reha-Vorbereitungslehrgang für besondere Zielgruppen - Entwicklung und Erprobung didaktisch-methodischer Reformsätze - Kremer, H.-Hugo; Zoyke, A. (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Individuelle Förderplanung - Rezeption und Einsatz im Übergangssystem - de Groot, C.; Kremer, H.-Hugo; Zoyke, A. (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Berufsorientierung als Herausforderung und Chance für die schulisch strukturierten Bildungsgänge des Übergangssystems - Kremer, H.-Hugo (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Wie der Übergang gelingen kann - Empirische Explorationen zur beruflichen Orientierung von Jugendlichen im Übergangssystem - Kremer, H.-Hugo; Rüschen, E. (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Kollektivstrukturen als Gestaltungselemente in der wirtschaftspädagogischen Begleitforschung - Beutner, Marc; Kremer, H.-Hugo (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Berufliches Lernen mit Web 2.0 - Medienkompetenz und berufliche Handlungskompetenz im Duell? - Pferdt, F. G.; Kremer, H.-Hugo (Jahrbuch Medienpädagogik 8. Medienkompetenz und Web 2.0)

Implementation von Curricula am Beispiel der Lernfeldinnovation - Buschfeld, D.; Kremer, H.-Hugo (Handbuch Berufs- und Wirtschaftspädagogik)

Bildung in Zeiten neuer Medien aus berufs- und wirtschaftspädagogischer Perspektive - Kremer, H.-Hugo (Bildung und Unterricht in Zeiten von Google und Wikipedia)

Tandem: Ausbildungsfähigkeit von Gefangenen und Gewaltprävention im Strafvollzug - Kremer, H.-Hugo; Gebbe, M.; Wirth, W. (Bewährungshilfe. Soziales - Strafrecht - Kriminalpolitik)

Individuelle Förderung - aber wie? Einblicke in das Innovationsprojekt InLab - Kremer, H.-Hugo; Frehe, Petra (Wirtschaft und Erziehung)

Kompetenzdiagnose als Basis individueller Förderung - Zum Geheimnis einer Black Box!? - Kremer, H.-Hugo; Zoyke, A. (Kompetenzermittlung für die Berufsausbildung. Verfahren, Probleme und Perspektive im nationalen, europäischen und internationalen Raum)

Online-Produktkonfiguratoren – Status quo und Entwicklungsperspektiven - Becker, Jörg; Knackstedt, Ralf; Müller, Oliver; Benölken, Alexander; Schmitt, Oliver; Thillainathan, Mayooran; Schulke, André (Vertriebsinformationssysteme)

An ontology-based natural language service discovery engine--design and experimental evaluation - Becker, Jörg; Müller, Oliver; Woditsch, Manuel (European Conference on Information Systems)

The Use of Instant Messaging in Working Relationship Development: A Case Study - Cho, Hee-Kyung; Trier, Matthias; Kim, Eunhee (Journal of Computer-Mediated Communication)

Struktur und Dynamik in der Netzwerkanalyse - Trier, Matthias (Handbuch Netzwerkforschung)

Towards a Systematic Approach for Capturing Knowledge-Intensive Business Processes - Trier, Matthias; Müller, Claudia (Practical Aspects of Knowledge Management)

Analyzing the Dynamics of Community Formation Using Brokering Activities - Trier, Matthias; Bobrik, Annette (Communities and Technologies 2007)

Hochschulforscher oder Hochschullehrer? Eine Panel-Daten-Analyse wirtschaftswissenschaftlicher Bachelor- und Masterkurse - Lück, Sonja (Hochschulmanagement)

Einheitlicher europäischer Bankenmarkt? Eine Einschätzung der Wettbewerbssituation vor und nach der Finanzkrise - Paul, Stephan; Uhde, André (Wirtschaftsdienst)
Die schwerste Finanz- und Wirtschaftskrise nach dem Zweiten Weltkrieg befindet sich nun schon in ihrem dritten Jahr und wird in weiten Teilen der Öffentlichkeit als Paradebeispiel für ein gravierendes Marktversagen eingestuft. Dies hat über die unmittelbaren staatlichen Rettungsmaßnahmen hinaus den Ruf nach "Mehr Staat in der Kreditwirtschaft!" verstärkt und vielfältige Vorschläge zur Ausweitung und Verschärfung der Beaufsichtigung der Banken hervorgerufen (zuletzt im September 2009 beim Finanzgipfel in Pittsburgh). Noch lässt sich nicht präzise genug abschätzen, welche staatlichen Hilfen für die Kreditwirtschaft erforderlich sein werden und welche Veränderungen in der Bankenregulierung noch vorgenommen werden müssen. Dennoch wird in diesem Beitrag der Versuch einer Skizze möglicher Auswirkungen auf die Wettbewerbssituation des europäischen und deutschen Bankenmarktes speziell im Retail-Segment unternommen. Um die durch die Finanzkrise hervorgerufenen Veränderungen einschätzen zu können, ist jedoch zunächst ein kurzer Blick auf die wichtigsten Etappen und Ergebnisse der europäischen Finanzmarktintegration erforderlich.
Keywords: Finanz- und Wirtschaftskrise; Bankenmarkt

Securitization and systematic risk in European banking: Empirical evidence - Uhde, André; Michalak, Tobias C. (Journal of Banking & Finance)
Using a unique dataset of 592 cash and synthetic securitizations issued by 54 banks from the EU-15 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a positive impact on the increase of European banks’ systematic risk. Baseline results hold when comparing estimated beta coefficients with a control group of similar non-securitizing banks. Building several sub-samples we additionally find that (a) the increase in systematic risk is more relevant for larger banks that repeatedly engage in securitization, (b) securitization is more important for small and medium financial institutions, (c) banks have a higher incentive to retain the larger part of credit risk as a quality signal at the beginning of the securitization business in Europe, and (d) the overall risk-shifting effect due to securitization is more distinct when the pre-event systematic risk is low.
Keywords: Credit risk transfer; Securitization; Systematic risk; Event study

Besteuerung multinationaler Unternehmen in der EU – eine vergleichende Analyse ausgewählter Reformvorschläge - Sureth-Sloane, Caren; Bäumer, Michaela (Zeitschrift für Betriebswirtschaft)

Capitalized investments with entry and exit options and paradoxical tax effects - Schneider, Georg; Sureth-Sloane, Caren (Review of Managerial Science)

Wie attraktiv sind Beteiligungsinvestitionen nach der Begrenzung der Verlustnutzung bei Anteilskäufen durch § 8c KStG? - Sureth-Sloane, Caren; Vollert, Pia (Corporate Finance biz)

The Impact of Tax Optimized Investment Projects on the Effective Group Tax Rate - Müller, Jens; Sureth-Sloane, Caren (Die Betriebswirtschaft)

Industrial services, product innovations, and firm profitability: A longitudinal analysis - Eggert, A.; Hogreve, J.; Ulaga, W.; Münkhoff, Eva (Frontiers Pre-Conference on Service and Solution Innovation, Karlstad)

Exploring the effects of referral reward programs on satisfied and dissatisfied customers - Garnefeld, I.; Münkhoff, Eva; Hogreve, J.; Eggert, A. (2010 AMA Winter Academic Conference, New Orleans, LA)

Disentangling the revenue and cost implications of the service transition: A latent growth analysis - Eggert, A.; Hogreve, J.; Ulaga, W.; Münkhoff, Eva (ISBM 2010 Academic Conference, Boston, MA)

Referral reward programs: A means for service recovery? - Münkhoff, Eva; Garnefeld, I.; Hogreve, J.; Eggert, A. (18th International Colloquium on Relationship Marketing (ICRM), Reading)

Legitimacy of Control - Schnedler, Wendelin; Vadovic, Radovan (Journal of Economics and Management Strategy)

Grenzüberschreitende Verlustverrechnungssysteme in Europa – Vorbilder für eine Reform der deutschen Organschaft? - Sureth-Sloane, Caren; Mehrmann, Annika; Dahle, Claudia (Steuer und Wirtschaft)

Monotonicity and Nash implementation in matching markets with contracts - Haake, Claus-Jochen; Klaus, Bettina (Economic Theory)

DIVIDING BY DEMANDING: OBJECT DIVISION THROUGH MARKET PROCEDURES - Haake, Claus-Jochen (International Game Theory Review)
We discuss a model, in which two agents may distribute finitely many objects among themselves. The conflict is resolved by means of a market procedure. Depending on the specifications, this procedure serves to achieve bargaining solutions such as the discrete Raiffa solution, the Kalai-Smorodinsky solution and the Perles-Maschler solution. The latter is axiomatized using the superadditivity axiom, which in the present context is readily interpreted as resolving a specific source of conflict potential.

Editorial Preface - Kundisch, Dennis

Standortwahl als Entscheidungsproblem des Logistikcontrollings - Betz, Stefan (Der Betriebswirt)

Optimale Darlehensbündel in der privaten Immobilienfinanzierung - Dzienziol, J.; Kundisch, Dennis (Kredit und Kapital)

Zur Preissetzung verschiedener Emittenten bei Indexzertifikaten auf den DAX - Kundisch, Dennis; Klein, C. (Zeitschrift für Bankrecht und Bankwirtschaft)

Der Tracking Error von indexnachbildenden Instrumenten auf den DAX - eine empirische Analyse des ETFs DAX EX sowie zehn Indexzertifikaten - Kundisch, Dennis; Klein, C. (Der Betrieb)

Productivity management for customer solutions --- Towards a performance management system for efficient service value networks - Becker, Jörg; Beverungen, Daniel; Blinn, Nadine; Knackstedt, Ralf; Nüttgens, Markus; Thomas, Oliver; Fellmann, Michael (29th International RESER Conference)

Configurative Service Engineering --- A Rule-Based Configuration Approach for Versatile Service Processes in Corrective Maintenance - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin (Proceedings of the 42th Hawaii International Conference on System Sciences)

A Framework for Design Research in the Service Science Discipline - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (Americas Conference on Information Systems)

Design Requirements to Support Information Flows for Providing Customer Solutions: A Case Study in the Mechanical Engineering Sector - Becker, Jörg; Beverungen, Daniel; Matzner, Martin; Müller, Oliver (Proceedings of the First International Symposium on Services Science (ISSS'09))

Model-Based Decision Support for the Customer-Specific Configuration of Value Bundles - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Enterprise Modelling and Information Systems Architectures)

Mikroanalytische Begleitung der Steuerpolitik am Beispiel der Erbschaftsteuerreform - Maiterth, Ralf; Houben, Henriette; Broekelschen, Wiebke; Müller, Jens; Sureth-Sloane, Caren (Statistik und Wissenschaft)
Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation | Deutschland | Germany
Keywords: Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation

Linkages between Financial Deepening, Trade Openness and Economic Development: Causality Evidence from Sub-Saharan Africa - Gries, Thomas; Kraft, Manfred; Meierrieks, Daniel (World Development)

The Optimal Distance to Port for Exporting Firms - Gries, Thomas; Naudé, Wim (Journal of Regional Science)

Explaining Regional Export Performance in a Developing Country: The Role of Geography and Relative Factor Endowments - Gries, Thomas; Naudé, Wim (Regional Studies)

Entrepreneurship and regional economic growth: towards a general theory of start-ups - Gries, Thomas; Naudé, Wim (Innovation: The European Journal of Social Science Research)

IT Productivity and Aggregation using Income Accounting - Kundisch, Dennis; Mittal, N.; Nault, B. (10th Workshop on Information Systems and Economics (WISE))

Enhancing the Quality of Financial Advice with Web 2.0 - An Approach considering Social Capital in the private Asset Allocation - Kundisch, Dennis; Zorzi, R. (Proceedings of the 15th Amercas Conference on Information Systems (AMCIS))

An Evaluation Framework for Tracker Certificates during the Financial Crisis and beyond - Kundisch, Dennis; Klein, C. (International Federation of Classification Societies 2009 Conference)

Technical Analysis as a Method of Risk Management - Dorfleitner, G.; Klein, C.; Kundisch, Dennis (Monetary Growth: Trends, Impacts and Policies)

Proceedings of the 4th International Workshop on Enterprise Applications and Services in the Finance Industry

Who Owns the Customer? Disentangling Customer Loyalty in Indirect Distribution Channels - Eggert, A; Henseler, J; Hollmann, S (Proceedings of the 17th International Colloquium in Relationship Marketing)

Can Successful Customer Acquisition Hurt the Existing Customer Base? - Woisetschläger, D; Garnefeld, I; Eggert, A (Proceedings of the 2009 AMA Summer Marketing Educators' Conference)

Referral reward programs: New customer acquisition by opportunism? - Garnefeld, I; Münkhoff, E; Hogreve, J; Eggert, A (Proceedings of the 15th Academy of Marketing Science (AMS) World Marketing Congress)

Musing on a Decade of Customer Value Research in Business Relationships: Where Do We Come From? Where Should We Go? - Eggert, A; Ulaga, W (Proceedings of the 4th International Conference on Business Market Management)

Customer Referral Programs and Customer Retention – Do Rewards Undermine the Retention Effect? - Garnefeld, I; Helm, S; Tax, S; Eggert, A (Proceedings of the 2009 AMA Winter Educators' Proceedings)

Unintended effects of referral reward programs: Exploring the impact of rewards on opportunistic behavior - Garnefeld, I; Münkhoff, E; Hogreve, J; Eggert, A (Proceedings of the 38th European Marketing Academy (EMAC) Conference)

Who Owns the Customer? Exploring Customer Loyalty in a Channel Context - Eggert, A; Henseler, J; Hollmann, S (Proceedings of the 38th European Marketing Academy (EMAC) Conference)

Acceptance of Remote Services – Perception, Adoption, and Continued Usage in Organizational Settings - Wünderlich, Nancy
The increasing employment of information and communication technologies in companies and households has led to considerable changes in the way services are conceived, developed, and delivered. Nancy V. Wünderlich employs a multi-method approach comprising an international qualitative study in Germany, USA and China and a longitudinal quantitative study to analyze remote services. She develops the Interactive Technology-Mediated Service Model (ITSUM) to provide a comprehensive approach of explaining both initial acceptance and repeated, continued usage of remote services in organizations. Finally, she derives managerial implications for remote service providers on how to increase remote service acceptance among their customers and facilitate the export of remote services.

Vorteil Interim Management - Kabst, Rüdiger; Thost, W; Isidor, R

Was zeichnet den erfolgreichen Interim Manager aus? - Kabst, Rüdiger; Isidor, R; Thost, W; Linné, H

Manager auf Zeit: Ignoriert oder akzeptiert? - Kabst, Rüdiger; Isidor, R; Thost, W; Nagel, R

International Fachkräfte gewinnen - Kabst, Rüdiger; Salow, S; Baum, M

Editorial: Motivieren trotz Krise - Kabst, Rüdiger